Expression of neu protein, epidermal growth factor receptor, and transforming growth factor alpha in breast cancer. Correlation with clinicopathologic parameters. - Lundy, J. (1991)
The major objectives of this study were twofold: to determine 1) if growth factors or growth factor receptors were expressed similarly or differently in a clinically well-characterized group of breast cancer patients and 2) if these phenotypic characteristics were associated with any of the commonly used prognostic parameters. Formalin-fixed paraffin-embedded tumor tissue from 51 node-positive breast cancer patients were analyzed for the expression of neu, epidermal growth factor-receptor (EGF-R), and transforming growth factor alpha (TGF alpha) using immunoperoxidase staining. Positive membranous staining for neu was observed in 15 (29%) tumors. Over-expression of neu was observed in high-grade, estrogen-receptor-negative tumors (P less than 0.05). Epidermal growth factor receptor was expressed in 22 (43%) of the tumors analyzed and found to a greater degree in estrogen-receptor-negative and high-grade tumors (P less than 0.025). A significant correlation between neu and EGF-R expression was also noted. Tumors expressing membranous staining of neu had a greater than 70% chance of expressing EGF-R (P less than 0.01). Expression of TGF alpha was found in 68% of tumors and TGF alpha was detected in grade 1 and 2 tumor to a greater degree than EGF-R. The authors conclude that assaying tumors for these antigens may give additional phenotypic characteristics that can give further insight into the biology of breast cancer.